2015
DOI: 10.1177/0394632015572074
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue syndrome: Features of a population of patients from northern Italy

Abstract: In this study we analyzed the clinical features of a population of Italian patients with chronic fatigue syndrome (CFS) diagnosed according to the CDC-1994 criteria. The aim was to investigate CFS patients and their relatives, in order to search for events related to the onset of the disease and to identify correlations with other diseases. The analysis was carried out by examining medical records belonging to 82 patients suffering from the syndrome. The documentation was collected between 2008 and 2011 and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…Seventy percent stated their mononucleosis was due to Epstein-Barr virus while 16% noted cytomegalovirus-associated mononucleosis .c The most common autoimmune illness was Hashimoto's thyroiditis with a prevalence of 15%. Others mentioned were vitiligo, celiac disease, psoriasis, ulcerative colitis, interstitial cystitis, Sjogren's syndrome, and multiple sclerosis .d Prevalence figures for conditions cited are from the following references: anxiety (24, 39, 41, 51), depression (21, 24, 40, 41), fibromyalgia (19, 24, 2628, 35, 39, 41, 51, 52), irritable bowel syndrome (19, 2529, 52), symptomatic infectious mononucleosis (25), migraine headaches (53), autoimmune conditions (25, 40, 54), chronic sinusitis (55), hay fever (55), hypothyroidism (general) (24, 41, 55), multiple chemical sensitivities (19, 27, 35, 55), sleep apnea (41, 56), TMJ (27, 28, 51), POTS (35, 42, 52, 57, 58) .e Prevalence figures for conditions are cited from the following references: anxiety (59), depression (59), fibromyalgia (60), irritable bowel syndrome (61), symptomatic infectious mononucleosis (62), migraine headaches (63), autoimmune conditions (64), chronic sinusitis (65), hay fever (65), hypothyroidism (general) (66), peripheral neuropathy (67), multiple chemical sensitivities (68), sleep apnea (69), TMJ (70), POTS (58) .f No study found addressing this topic specifically .…”
Section: Personal Medical Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy percent stated their mononucleosis was due to Epstein-Barr virus while 16% noted cytomegalovirus-associated mononucleosis .c The most common autoimmune illness was Hashimoto's thyroiditis with a prevalence of 15%. Others mentioned were vitiligo, celiac disease, psoriasis, ulcerative colitis, interstitial cystitis, Sjogren's syndrome, and multiple sclerosis .d Prevalence figures for conditions cited are from the following references: anxiety (24, 39, 41, 51), depression (21, 24, 40, 41), fibromyalgia (19, 24, 2628, 35, 39, 41, 51, 52), irritable bowel syndrome (19, 2529, 52), symptomatic infectious mononucleosis (25), migraine headaches (53), autoimmune conditions (25, 40, 54), chronic sinusitis (55), hay fever (55), hypothyroidism (general) (24, 41, 55), multiple chemical sensitivities (19, 27, 35, 55), sleep apnea (41, 56), TMJ (27, 28, 51), POTS (35, 42, 52, 57, 58) .e Prevalence figures for conditions are cited from the following references: anxiety (59), depression (59), fibromyalgia (60), irritable bowel syndrome (61), symptomatic infectious mononucleosis (62), migraine headaches (63), autoimmune conditions (64), chronic sinusitis (65), hay fever (65), hypothyroidism (general) (66), peripheral neuropathy (67), multiple chemical sensitivities (68), sleep apnea (69), TMJ (70), POTS (58) .f No study found addressing this topic specifically .…”
Section: Personal Medical Historymentioning
confidence: 99%
“…d Prevalence figures for conditions cited are from the following references: anxiety (24, 39, 41, 51), depression (21, 24, 40, 41), fibromyalgia (19, 24, 2628, 35, 39, 41, 51, 52), irritable bowel syndrome (19, 2529, 52), symptomatic infectious mononucleosis (25), migraine headaches (53), autoimmune conditions (25, 40, 54), chronic sinusitis (55), hay fever (55), hypothyroidism (general) (24, 41, 55), multiple chemical sensitivities (19, 27, 35, 55), sleep apnea (41, 56), TMJ (27, 28, 51), POTS (35, 42, 52, 57, 58) .…”
Section: Personal Medical Historymentioning
confidence: 99%
See 1 more Smart Citation
“…ME/CFS is estimated to affect as many as 2.5 million people in the United States, which corresponds to about 1% of the total U.S. population (Vincent et al, 2012;Ganiats, 2015;Komaroff, 2015). Other studies (Jason et al, 2009), including those conducted in Minnesota (Vincent et al, 2012), as well as in the United Kingdom (Nacul et al, 2011;Collin et al, 2017), Norway (Bakken et al, 2014), and Italy (Capelli et al, 2015), report a lower incidence. Women are apparently more susceptible than men, with an estimated ratio of 4:1 (Germain et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…В нашем исследовании, как и в опубликованных работах других авторов, в группе пациентов со слабостью преобладают женщины средних лет [29][30][31]. Возможно, гормональный фон, склонность к эмоциональным реакциям у женщин способствуют развитию СХУ [32,33].…”
Section: Discussionunclassified